Marketing Digital y su Incidencia en el Volumen de Ventas del Comercial de Calzado "Three Brothers - Arbelaez Moran, Freddy Alex (2017)
he marketing according to history has been used since the beginning of the commerce, in that time has been evolving and adapting to different changes, one of them is the massive use of the Internet, also known as the network of interconnection where everybody is linked. The conventional marketing of little has adapted to what are the new media and communication among which we find, emails, social networks and varieties of media and applications which together is also known as digital marketing. Digital marketing or online marketing is a way of looking much further, is to embrace a large amount of information with ease, using a variety of methods and strategies of sales, that go according to needs and desires of the target audience in this context in our country according to the INEC are registered 45.2% of companies that indicate commercial transactions through the Internet